2017
DOI: 10.1186/s12967-017-1157-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive in vivo imaging of cardiac stem/progenitor cell biodistribution and retention after intracoronary and intramyocardial delivery in a swine model of chronic ischemia reperfusion injury

Abstract: BackgroundThe safety and efficacy of cardiac stem/progenitor cells (CSC) have been demonstrated in previous preclinical and clinical assays for heart failure. However, their optimal delivery route to the ischemic heart has not yet been assessed. This study was designed to determine by a non-invasive imaging technique (PET/CT) the biodistribution and acute retention of allogeneic pig CSC implanted by two different delivery routes, intracoronary (IC) and intramyocardial (IM), in a swine preclinical model of chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 36 publications
1
21
1
Order By: Relevance
“…However, despite the simplicity, acute ischemia due to stop-flow cell injection technique (repeated occlusion/reperfusion of the infarct-related artery) and the potential for intravascular cell clustering and distal embolization is a concern (Gyongyosi et al, 2010a , 2011 ). Our results are in line with the observations that higher myocardial accumulation of injected cells with consequent better efficacy profile could be demonstrated if the transplanted cells were injected intramyocardially (Collantes et al, 2017 ; Kanelidis et al, 2017 ). In addition to the previous works, we have revealed that intramyocardial injections led to less biodistribution in remote organs, and that intramyocardial injections resulted in higher expression of angiogenic substances in that myocardial areas, where the cells were injected and retained.…”
Section: Discussionsupporting
confidence: 91%
“…However, despite the simplicity, acute ischemia due to stop-flow cell injection technique (repeated occlusion/reperfusion of the infarct-related artery) and the potential for intravascular cell clustering and distal embolization is a concern (Gyongyosi et al, 2010a , 2011 ). Our results are in line with the observations that higher myocardial accumulation of injected cells with consequent better efficacy profile could be demonstrated if the transplanted cells were injected intramyocardially (Collantes et al, 2017 ; Kanelidis et al, 2017 ). In addition to the previous works, we have revealed that intramyocardial injections led to less biodistribution in remote organs, and that intramyocardial injections resulted in higher expression of angiogenic substances in that myocardial areas, where the cells were injected and retained.…”
Section: Discussionsupporting
confidence: 91%
“…It has been always assumed that retention of transplanted cells is more efficient using intramyocardial administration, since the coronary circulation cannot efficiently wash out the cells. Some reports, however, have described an unexpected rapid venous washout, rendering a similar retention by the two methods [43, 44]. Another route that has been proposed to safely administer high cell doses is the intrapericardial administration [45, 46], but few reports have evaluated this approach to date, and mostly in a chronic setting.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac stem cells were also loaded with 18 F-FDG and imaged by PET to quantify their biodistribution and assess the retention of implanted cells in a model of chronic myocardial infarction in pigs. Acute cell retention was shown not to correlate with cell engraftment, which is improved by IM injection (17).…”
Section: Stem Cell Therapiesmentioning
confidence: 85%
“…With its fast and efficient uptake and good retention, 18 Flabeled fluoro-2-deoxy-2-D-glucose ( 18 F-FDG) may be used to label cells in vitro to monitor cell traffic in vivo. For instance, cardiac stem cells were labeled and their biodistribution and retention was quantified in a pig model of chronic myocardial infarction (17). A potential drawback of 18 F-FDG for assessing cell therapies following implantation is the local retention of radiotracer released from the cells.…”
Section: Radioactive (Spect Pet)mentioning
confidence: 99%